Process quality in Portuguese preschool classrooms serving children at-risk of poverty and social exclusion and children with disabilities - Cadima, J. (2018)
This study investigates process quality and structural features of classrooms serving children at-risk of poverty and social exclusion and children with disabilities in Portugal. We examine (a) whether the three-domain structure of a widely used standard observational tool, the Classroom Assessment Scoring System (CLASS; Pianta, LaParo, & Hamre, 2008) describes adequately teacher–child interactions in those classrooms and (b) associations between CLASS domains and structural features, including teacher education and group size. The study was conducted in 178 preschool classrooms. Data included classroom observations using the CLASS Pre-K and teacher reports on structural features. Confirmatory factor analysis supported the three domains of teacher–child interactions. In addition, the CLASS domains described teacher–child interactions equally well across classrooms serving children with disabilities and children at-risk of poverty and social exclusion. Finally, we found modest associations between structural features and CLASS organizational and instructional support, suggesting a complex interplay among structural features in predicting levels of teacher–child interactions.